Non-dopaminergic Alterations in Depression-Like FSL Rats in Experimental Parkinsonism and L-DOPA Responses - Schintu, Nicoletta; Zhang, Xiaoqun; Stroth, Nikolas; Mathé, Aleksander A.; Andrén, Per E.; Svenningsson, Per (Frontiers in Pharmacology, 2020)
Depression is a common comorbid condition in Parkinson´s disease (PD). Patients with depression have a two-fold increased risk to develop PD. Further, depression symptoms often precede motor symptoms in PD and are frequent at all stages of the disease. However, the influence of a depressive state on the responses to antiparkinson treatments is largely unknown. In this study, the genetically inbred depression-like Flinders Sensitive Line (FSL) rats and control Flinders Resistant Line (FRL) rats were studied in models of experimental parkinsonism. FSL rats showed a potentiated tremorgenic response to tacrine, a cholinesterase inhibitor used experimentally to induce 6 Hz resting tremor reminiscent of parkinsonian tremor. We also studied rats lesioned with 6-OHDA to induce hemiparkinsonism. No baseline differences in dopaminergic response to acute apomorphine or L- DOPA was found. However, following chronic treatment with L-DOPA, FRL rats developed sensitization of turning and abnormal involuntary movements (AIMs); these effects were counteracted by the anti-dyskinetic 5-HT1A agonist/D2 partial agonist sarizotan. In contrast, FSL rats did not develop sensitization of turning and only minor AIMs in response to L-DOPA treatment. The roles of several non-dopamine systems underlying this discrepancy were studied. Unexpectedly, no differences of opioid neuropeptides or serotonin markers were found between FRL and FSL rats. The marked behavioral difference between the FRL and FSL rats was paralleled with the striatal expression of the established marker, c-fos, but also the GABAergic transporter, vGAT, and a hitherto unknown marker, tamalin, that is known to regulate mGluR 5 receptor function and postsynaptic organization. This study demonstrates that behavioral and transcriptional responses of non-dopaminergic systems to experimental parkinsonism and L-DOPA are modified in a genetic rat model of depression.